Usage patterns and constraints of harnessing social media channels for entrepreneurship among youths in Nigeria - Carol Odoyi (EcoProfit: Sustainable and Environment Business, 2026)
Background: In recent years, social media channels have emerged as powerful tools for entrepreneurship, but every innovation of man has come with two-faced implications; on one side are opportunities, while on the other side are limitations. Accordingly, this paper presents the outcome of research on the usage patterns and constraints of harnessing social media channels for entrepreneurship among youths in Nigeria. The objectives of the study were to identify the usage patterns as well as the constraints of harnessing social media channels for entrepreneurship among youths in Nigeria. Methods: The study was anchored on the uses and gratifications theory. It adopted the descriptive survey research design and multi-stage sampling technique to derive responses from a sample size of 384 youths aged between 18 and 29 years. The instruments for data collection were focus group discussions and the questionnaire, while data were analysed using explanation-building and statistical techniques of mean and standard deviation. Findings: The findings of the study revealed that some youths in Rivers State use social media channels for microblogging, marketing, digital influencing, and brand promotion. However, challenges such as cyberbullying and internet fraud significantly hinder entrepreneurial outcomes. Conclusion: Based on the findings, the researcher concluded that while social media gratifies a wide variety of youths entrepreneurial needs, youths are, on the other hand, sacrificing so much for these gratifications as it imposes trade-offs on their mental health and productivity. Novelty/Originality of this article: The study recommends digital literacy programmes, stronger regulatory frameworks, and entrepreneurial mentorship to maximise benefits and mitigate risks.